ELASTIC WAVE BAND GAPS IN A TWO-DIMENSIONAL MAGNETOELECTROELASTIC PHONONIC CRYSTAL - de Miranda Júnior, Edson Jansen Pedrosa; Santos, José Maria Campos dos (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In this study we investigated the band structure of elastic waves propagating in a magnetoelectroelastic phononic crystal (MPC), consisting of a polymer matrix reinforced by BaTiO3”“CoFe2O4 inclusions in a square, triangular and honeycomb lattices. We also studied the influence of the inclusion geometry cross section ”“ circular, hollow circular, square and rotated square with a 45° angle of rotation with respect to the x, y axes. The plane wave expansion (PWE) method was used to solve the constitutive equations of a magnetoelectroelastic material considering the wave propagation in the xy plane (longitudinal-transverse vibration, XY mode, and transverse vibration, Z mode). The complete band gaps between the XY and Z modes were observed to all types of inclusion and the best performance depends on the lattice. For square lattice, the best performance was found for square inclusion in lower frequencies, for triangular lattice, the circular, square and rotated square present, approximately, the same behavior and for honeycomb lattice, the best performance was found for circular inclusion.